IMPLEMENTATION OF EDUCATIONAL INSTITUTION LEADERS IN IMPROVING EDUCATION QUALITY MANAGEMENT FOR TEACHERS - Rohaemi Rohaemi; Eneng Muslihah; Machdum Bachtiar; Yuyun Rohmatul Uyuni; Abdul Muin (Jurnal Konseling Pendidikan Islam, 2026)
Education plays a strategic role in shaping quality human resources through the implementation of educational quality management and the improvement of teacher quality as the main implementers of the learning process. This study was motivated by the importance of the role of educational institution leaders in fostering, directing, and empowering teachers to achieve optimal education quality. The purpose of this study was to analyze the implementation and strategies used by educational institution leaders in improving quality management among teachers at MTs Negeri 1 and MTs Negeri 2 in Serang Regency. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that educational institution leaders have implemented quality management by applying five competencies of madrasah principals, namely personality, managerial, entrepreneurial, supervisory, and social competencies. This implementation is realized through systematic program planning, continuous academic supervision, and teacher professional development through MGMP activities, workshops, seminars, and performance monitoring. Improvements in education quality were also made through the integrated management of inputs, processes, outputs, and outcomes. Supporting factors in the implementation of quality management included the leadership competencies of madrasah principals, teacher commitment and participation, a collaborative work culture, and the use of technology and managerial innovation. Meanwhile, the inhibiting factors include differences in teachers' understanding of quality management, limited time for professional development, limited infrastructure, and resistance to change. Overall, participatory and collaborative leadership has proven to be able to improve the quality of education and teachers in madrasahs.